Atom ionization by strong laser pulses - gauge invariant description - Ślęczka, Marcin; Bechler, Adam (Photonics Letters of Poland, 2013)
We present recent results of our studies on the matter interaction with strong laser pulses. It has been known that the results obtained with use of Strong Field Approximation which underlay the Keldysh-Faissal-Reiss theory (KFR), leads to the gauge dependent expression for the probability amplitude. We propose new approach to this problem and develop new method to obtain expression which are gauge independent. We present examples of numerical calculations which show good agreement of our model with TDSE results. Full Text: PDF References L.V. Keldysh, "Diagram Technique for Nonequilibrium Processes", Zh. Eksp. Theor. Fiz. 47, 1945(1964) (L.V. Keldysh, Sov. Phys. JETP 20 137 (1965)) DirectLink F.H.M. Faisal, "Multiple absorption of laser photons by atoms", J. Phys. B; At. Mol. Phys. 6 L89 (1973) CrossRef H.R. Reiss, "Effect of an intense electromagnetic field on a weakly bound system", Phys. Rev. A 22, 1786 (1980) CrossRef D. Bauer, D.B. Milošević and W. Becker, "Strong-field approximation for intense-laser–atom processes: The choice of gauge", Phys. Rev. A 72 023415 (2005) CrossRef H.R. Reiss, "Velocity-gauge theory for the treatment of strong-field photodetachment", Phys. Rev. A 76 033404 (2007) CrossRef J. Bauer, "Qualitatively different theoretical predictions for strong-field photoionization rates", Phys. Rev. A 84 025403 (2011) CrossRef W. Becker, F. Grasbon, R. Kopold, D.B. Milošević, G.G. Paulus and D. Bauer, "Above-threshold ionization: From classical features to quantum effects", Adv. At. Mol. Opt. Phys. 48, 35 (2002) CrossRef A. Bechler, M. Ślęczka, "A manifestly gauge-invariant description of interaction of atomic systems with strong fields in the dipole approximation", Phys. Letters A 375, 1579 (2011) CrossRef D. Bauer, P. Koval, "Qprop: A Schrödinger-solver for intense laser–atom interaction", Computer Physics Communications, 174 (5) 396 (2006) CrossRef A. Bechler, M. Ślęczka, "Application of the gauge-invariant formalism to the description of ionization by ultrastrong few-cycle pulses", Phys. Rev. A 87, 025402 (2013) CrossRef F.H.M. Faisal, "Gauge-invariant intense-field approximations to all orders", J. Phys. B: At. Mol. Opt. Phys. 40, F145 (2007) CrossRef Y.V. Vanne, A. Saenz, "Generalized gauge-invariant formulations of the strong-field approximation", Phys. Rev. A 79, 023421 (2009) CrossRef